KESTABILAN MODEL DUA MANGSA â SATU PEMANGSA DENGAN PEMANENAN LINEAR PADA MANGSA - , FARDINAH ([Yogyakarta] : Universitas Gadjah Mada, 2013)
In this thesis, it was discussed two preys â one predator model that was a development of predator prey Lotka Volterra model. In this model was assumed that the prey grew logistically and it was used the function of response that depend on prey. The model was divided in two cases, i.e ecosystem with the absence of harvesting and ecosystem with the presence of harvesting. Based on the two cases, the existence and the stability of equilibrium point was investigated.